2007
DOI: 10.1007/s10551-007-9578-y
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Ethical Decision-making Processes in the United States and Egypt

Abstract: In this comparative survey of 191 Egyptian and 92 U.S. executives, we explore the relationship between national culture and ethical decision-making within the context of business. Using Reidenbach and Robin's (1988) multi-criteria ethics instrument, we examine how differences on two of Hofstede's national culture dimensions, individualism/collectivism, and power distance, are related to the manner in which business practitioners make ethical decisions. Egypt and the U.S. provide an interesting comparison becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 40 publications
0
37
0
2
Order By: Relevance
“…Local hotels may, therefore, be pessimistic (or perhaps realistic) about the extent to which a green reputation actually lead to economic benefits. It is generally observed that most local companies in Egypt lack marketing professionalism (Beekun et al, 2008;Marta et al, 2004) and hence find difficulties in accessing markets with special interests. If this is the situation, business survival becomes the core issue for these companies; local companies have to compete intensely for a market share and the environment would not be of course the selling point.…”
Section: Discussionmentioning
confidence: 99%
“…Local hotels may, therefore, be pessimistic (or perhaps realistic) about the extent to which a green reputation actually lead to economic benefits. It is generally observed that most local companies in Egypt lack marketing professionalism (Beekun et al, 2008;Marta et al, 2004) and hence find difficulties in accessing markets with special interests. If this is the situation, business survival becomes the core issue for these companies; local companies have to compete intensely for a market share and the environment would not be of course the selling point.…”
Section: Discussionmentioning
confidence: 99%
“…Although several empirical comparisons have been completed of ethics of Americans versus non-American business people [38,39], and American versus non-American consumers [40], the most common studies have been of American and non-American business students in cross-national comparisons of business ethics. Indeed, in a comprehensive review of how and why cultural differences arise, Jackson [41] developed and tested a model of ethical decision-making in 10 countries.…”
Section: Nationality and Eco-behaviourmentioning
confidence: 99%
“…that Muslims are more idealistic and less relativistic. The Islamic tradition places ethical/social activity ahead of individual profit maximization (Beekun et al 2008;Rice 1999), and Islam urges strict adherence to the ethical injunctions of the Quran. In Libya, Islam is the major source of the written laws and most of the legal environment surrounding business transactions (Kilani 1988).…”
Section: Individual Variablesmentioning
confidence: 99%